Implementation of Indonesian Nursing Diagnosis Standards in Identifying Sleep Pattern Disturbance Among Hypertensive Patients - Cindi Fatma Sari; Nur Khoiriyah; Syaifuddin Kurnianto; Erik Kusuma; Eko Prasetya Widianto (Fundamental and Management Nursing Journal, 2026)
Introduction: Sleep disturbances are strongly associated with poor blood pressure control and can worsen the clinical outcomes of hypertensive patients. This study aimed to analyze the application of the Indonesian Nursing Diagnosis Standards (Standar Diagnosis Keperawatan Indonesia or SDKI) in identifying Sleep Pattern Disturbance among hypertensive patients as documented by nursing students. Methods: This descriptive retrospective study utilized secondary data from 169 final year nursing student report’s archived from the year 2023 to 2024. Data were derived from Diploma Nursing Program (D-III), Faculty of Nursing, Universitas Jember, Indonesia. Data were extracted and analyzed using descriptive statistics. Results: The results showed that all nine cases involved patients over 50 years of age, predominantly women (8 out of 9). The most frequent symptoms recorded were difficulty initiating or maintaining sleep (100%), non-restorative sleep (78%), changes in sleep pattern (78%), frequent awakenings (56%), and feeling unrested (56%). Poor sleep control was the primary contributing factor (78%), followed by environmental factors such as noise and unpleasant odors (11% each). All reports consistently documented Sleep Pattern Disturbance as the sole nursing diagnosis using SDKI. Conclusions: Nursing students have begun to apply standardized terminology; however, the limited range of diagnoses and contributing factors suggests a need to strengthen supervision, comprehensive assessment, and diagnostic reasoning skills in nursing education. Future studies with larger samples and primary data are recommended to explore further the integration of SDKI with interventions (SIKI) and outcomes (SLKI).